Maria Montessori. For a change of educational paradigm - Elia, Sandra (Formazione & insegnamento, 2017)
This paper analyzes the pedagogical thinking of Maria Montessori and the evidence of her method. The educator gives to the teaching-learning process a decisive role in any deliberate action with transformative educational purposes. The Montessori Method leads to a new education because it allows the child to build his skills, in progressive autonomy, with his caregiver.